2018
DOI: 10.1186/s12942-018-0139-7
|View full text |Cite
|
Sign up to set email alerts
|

Food environments and dietary intakes among adults: does the type of spatial exposure measurement matter? A systematic review

Abstract: BackgroundThe relationships between food environments and dietary intake have been assessed via a range of methodologically diverse measures of spatial exposure to food outlets, resulting in a largely inconclusive body of evidence, limiting informed policy intervention.ObjectiveThis systematic review aims to evaluate the influence of methodological choice on study outcomes by examining the within-study effect of availability (e.g., counts) versus accessibility (e.g., proximity) spatial exposure measures on ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 82 publications
3
57
0
1
Order By: Relevance
“…Our measure of availability (counts) produced more important associations than our measure of accessibility (distance). These results are in line with the ones shown in the previous review [49], documenting effect sizes from accessibility measures to be smaller than effects from availability measures. Prior research has also shown different associations between neighborhood-level socioeconomic status and food access according to the accessibility dimension measured [54].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our measure of availability (counts) produced more important associations than our measure of accessibility (distance). These results are in line with the ones shown in the previous review [49], documenting effect sizes from accessibility measures to be smaller than effects from availability measures. Prior research has also shown different associations between neighborhood-level socioeconomic status and food access according to the accessibility dimension measured [54].…”
Section: Discussionsupporting
confidence: 92%
“…To the best of our knowledge, this is the first study to examine the retail food environment surrounding schools across an entire Southern European city like Madrid. According to a recent systematic review by Bivoltsis et al [49], there is no current consensus on the use of different exposure measures for food environment. Therefore, following their recommendations, we used a multimethod approach and decided to measure the effect of two dimensions of spatial access, availability and accessibility.…”
Section: Discussionmentioning
confidence: 99%
“…36 Compared with other measures of the fast-food environment, proximity measures may also produce more conservative estimates of association with relevant outcomes. 37 In a regional subsample of UK Biobank, others have recently improved on this measurement of the food environment and found stronger associations. 38 In this study, where the main effect sizes are relatively small, even the reasonably strong interaction effects we observed translate to small differences between high-risk and low-risk groups.…”
Section: Discussionmentioning
confidence: 99%
“…The availability and access to nutritious food (e.g., fruits and vegetables) can facilitate nutritionally-sound food choices [10,11,12,13,14,15]. Because of their expected effects on diet quality and security, research on the impact of food systems on the availability and accessibility of nutritious food in vulnerable populations has been recently emphasized [16].…”
Section: Introductionmentioning
confidence: 99%